Inside looking out : jailed fathers' perceptions about separation from their children - Martin, Jamie S. (Criminal justice (LFB Scholarly Publishing LLC), 2001)
Annotation Martin (criminology, Indiana U. of Pennsylvania) explores and describes the meaning and significance of the paternal role to jailed fathers, and how the experience of being jailed affects that role. She points out that when most people suffer stress, they turn to family members for assistance and support, but that prisoners do not have ready access to their families. As she anticipated, she found that the father's role in the family before he was incarcerated influences his incarceration experience. c. Book News Inc.